IMPROVING INFORMATION SUPPLY PUBLIC PROCUREMENT IN UKRAINE - Жук, Артем (Socio-economic relations in the digital society, 2019)
Theoretical and practical aspects, regulatory and legal peculiarities of public procurements in Ukraine with the use of the electronic system "ProZorro" are researched and generalized. The urgent problems of the public procurement system of Ukraine are considered and the ways of their solution are proposed. The analysis and proposed introduction of eff ective changes to the components of the form of submission and preparation of the annual procurement plan. Proposals were off ered on improving the information provision of the ProZorro process, in particular, the formation of an annual procurement plan. Measures to improve the system of public procurement are substantiated. Th e advantages of introducing innovations regarding the availability of information in the system of electronic purchases are generalized.